PERLINDUNGAN HUKUM BAGI KARYAWAN YANG DITAHAN IJAZAHNYA OLEH PERUSAHAAN - Junaidi, Junaidi (Solusi, 2018)
A work agreement is an agreement between a worker / laborer and an employer or employer that contains the work conditions, rights and obligations of the parties. The work agreement was made to obtain certainty regarding what was promised, both parties must respect each other. In the work agreement that must be considered is not violating the rule of law, each party must agree and may not be forced or forced, the contents of the work agreement must be clear, so that there is no misunderstanding in the future which results in default. An agreement in a company ideally protects the interests of all parties involved in the agreement because an agreement should be made based on the agreement between the two parties. The substance of the work agreement made may not conflict with the applicable labor regulations. Therefore work relations must contain the principle of justice, harmonization of the elements in industrial relations (employers, workers / laborers and the government).